Should Heartbeats/Training Session Be Considered When Comparing the Cardiovascular Benefits of High-Intensity Interval Aerobic and Moderate-Intensity Continuous Training? A Critical Appraisal - Rodrigues, Jhennyfer Aline Lima (Sports Med Open, 2020)
The prescription of physical training as a therapeutic measure in the treatment and control of chronic degenerative diseases, mainly cardiovascular disease and metabolic disease, is an increasingly used clinical approach, often preceding the pharmacological prescription. Despite the advances in exercise physiology and cardio functional performance in recent decades, the main challenge is to identify the most appropriate modality, intensity, and training volume for each pathophysiological situation. In this case, the superiority of high-intensity interval training (HIIT) over moderate-intensity continuous training (MICT) has been questioned, since many studies have shown similar results in the different physiological parameters evaluated, especially regarding cardiorespiratory fitness, cardiovascular autonomic control, and cardiac morpho functionality. The cause of conflicting results observed by different studies may be related to standardization, application, and comparison of the two protocols. HIIT would have a higher number of heartbeats compared to MICT, when maintaining high heart rate is disregarded. In this since, our hypothesis for the greatest gains in cardiorespiratory fitness and in the autonomic and cardiovascular adaptations promoted by HIIT is based on the higher volume of training performed as a function of the higher number of heartbeats per unit of time, since the intermittence was calculated based on a percentage of maximum heart rate or reserve heart rate. Nevertheless, the intermittency between the established heart rate percentages is not necessarily accompanied by the intermittent heart rate. Therefore, considering and matching the number of heartbeats performed per training session in both models seems to be a more appropriate way to compare the two training protocols.